Analisis Strategi Pemasaran Usaha Mau Tahu Banget - Hananing Galih Pramesti; Siti Fatimah Nurhayati (Universitas Muhammadiyah Surakarta, 2024)
One food that is well known throughout Indonesia which is made from soybeans is called tofu. The public saw the prospects for the processed tofu business, which resulted in many competitors selling various processed tofu. As a result, it is very difficult to sustain this business. Sellers of processed products must realize that they must use marketing strategies to defend themselves and attract new customers in order to compete. SWOT analysis was used to determine marketing strategies so it was found that the